2022
DOI: 10.1101/2022.10.04.510762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Piezo2 voltage-block regulates mechanical pain sensitivity

Abstract: PIEZO2 mechanosensitive channels are required for normal touch sensation. However, PIEZO2 channels are almost completely blocked at negative resting membrane potentials. We show that PIEZO2 voltage-block can be relieved by mutations at a conserved Arginine (R2756) which dramatically sensitizes the channel to mechanical stimuli. We generated Piezo2R2756H/R2756H and Piezo2R2756K/R2756K knock-in mice to ask how voltage regulates the endogenous mechanosensitivity of sensory neurons. Surprisingly, mechanosensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Our functional analysis demonstrated that Piezo2 positive endothelial cells possess fast mechanosensitive currents that have sensitivities and kinetics similar to Piezo2dependent currents in sensory cells 63,68,73 . However, many cardiac endothelial cells that had never expressed Piezo2 also exhibited mechanosensitive currents (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our functional analysis demonstrated that Piezo2 positive endothelial cells possess fast mechanosensitive currents that have sensitivities and kinetics similar to Piezo2dependent currents in sensory cells 63,68,73 . However, many cardiac endothelial cells that had never expressed Piezo2 also exhibited mechanosensitive currents (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…5 a -g). Human pathogenic gain-of-function mutations in PIEZO2, documented in human patients 35,39,72 , dramatically increase the channels' sensitivity to mechanical force 73 . By introducing this gain of function mutation into mice we show here that PIEZO2 hypersensitivity can also lead to a disruption of heart development (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size rather than the charge of the residue seems to yield the effect, as R2482K or R2482Q both slow down inactivation significantly (Moroni et al, 2018) [11]. In addition, the effect of R2482 is conserved in PIEZO2 as mutating the homologous mouse PIEZO2 R2756 to histidine (R2756H) or lysine (R2756K) slows down the inactivation of a PIEZO1/PIEZO2 chimera [34]. On the other hand, neutralizing the positive charge on K2479 by mutating it to glutamine (K2479Q) or reverting the charge by mutating it to glutamic acid (K2479E) abolished the voltage dependence of PIEZO1 inactivation [11].…”
Section: Intrinsic Mechanisms Underlying Inactivation Of the Piezo Ch...mentioning
confidence: 99%
“…The C-terminus of the protein is composed of an extracellular cap domain, the pore-forming inner transmembrane helix (IH) and outer transmembrane helix (OH), and an intracellular C-terminal domain. Both PIEZO1 and PIEZO2 possess voltage-dependent inactivation [27][28][29][30][31][32][33][34]. The whole-cell patch clamp with indentation shows a more rapid inactivation for PIEZO2, which has an inactivation time constant of around 5 ms compared to PIEZO1 of around 15 ms at a holding potential of −80 mV [29,35].…”
Section: Introductionmentioning
confidence: 95%